THE INTERRELATION BETWEEN FORENSIC MEDICINE AND PATHOPHYSIOLOGY - Miraxmedova Nargiz Rizoyevna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract Forensic medicine and pathophysiology are closely interconnected disciplines that together provide deep insights into the mechanisms of injury, disease, and death. Pathophysiology, which studies functional changes in the body resulting from pathological processes, forms the scientific basis for interpreting many findings in forensic examinations. This paper explores how understanding pathophysiological mechanisms enhances forensic diagnostics, particularly in establishing the cause and mechanism of death, injury assessment, and forensic interpretation of disease-related deaths.